A review on the recent advances in HPLC, UHPLC and UPLC analyses of naturally occurring cannabinoids (2010–2019). Issue 4 (17th December 2019) - Nahar, Lutfun; Onder, Alev; Sarker, Satyajit D.
Abstract: Introduction: Organic molecules that bind to cannabinoid receptors are called cannabinoids, and they have similar pharmacological properties like the plant, Cannabis sativa L. Hyphenated liquid chromatography (LC), incorporating high‐performance liquid chromatography (HPLC) and ultra‐performance liquid chromatography (UPLC, also known as ultrahigh‐performance liquid chromatography, UHPLC), usually coupled to an ultraviolet (UV), UV‐photodiode array (PDA) or mass spectrometry (MS) detector, has become a popular analytical tool for the analysis of naturally occurring cannabinoids in various matrices. Objective: To review literature on the use of various LC‐based analytical methods for the analysis of naturally occurring cannabinoids published since 2010. Methodology: A comprehensive literature search was performed utilising several databases, like Web of Knowledge, PubMed and Google Scholar, and other relevant published materials including published books. The keywords used, in various combinations, with cannabinoids being present in all combinations, in the search were Cannabis, hemp, cannabinoids, Cannabis sativa, marijuana, analysis, HPLC, UHPLC, UPLC, quantitative, qualitative and quality control. Results: Since 2010, several LC methods for the analysis of naturally occurring cannabinoids have been reported. While simple HPLC‐UV or HPLC‐UV‐PDA‐based methods were common in cannabinoids analysis, HPLC‐MS, HPLC‐MS/MS, UPLC (or UHPLC)‐UV‐PDA, UPLC (or UHPLC)‐MS and UPLC (or UHPLC)‐MS/MS, were also used frequently. Applications of mathematical and computational models for optimisation of different protocols were observed, and pre‐analyses included various environmentally friendly extraction protocols. Conclusions: LC‐based analysis of naturally occurring cannabinoids has dominated the cannabinoids analysis during the last 10 years, and UPLC and UHPLC methods have been shown to be superior to conventional HPLC methods. Abstract : Organic molecules, synthetic, semisynthetic or natural, that bind to cannabinoid receptors are called cannabinoids, and they have similar pharmacological properties as produced by the plant, Cannabis sativa L. Hyphenated liquid chromatography (LC), incorporating high performance liquid chromatography (HPLC) and ultra performance liquid chromatography (UPLC, also known as ultra high performance liquid chromatography, UHPLC), usually coupled to a UV, UV‐PDA or MS detector, hasbecome a popular analytical tool for the detection and quantification of naturally occurring cannabinoids in various matrices. This review article presents a critical review of literature on the use of various LC‐based analytical methods for the analysis of naturally occurring cannabinoids published since 2010.